New bacteriophage-derived lysins, LysJ and LysF, with the potential to control Bacillus anthracis - Nakonieczna, Aleksandra; Topolska-Woś, Agnieszka; Łobocka, Małgorzata (Applied microbiology and biotechnology, 2024)
Bacillus anthracis is an etiological agent of anthrax, a severe zoonotic disease that can be transmitted to people and cause high mortalities. Bacteriophages and their lytic enzymes, endolysins, have potential therapeutic value in treating infections caused by this bacterium as alternatives or complements to antibiotic therapy. They can also be used to identify and detect B. anthracis. Endolysins of two B. anthracis Wbetavirus phages, J5a and F16Ba which were described by us recently, differ significantly from the best-known B. anthracis phage endolysin PlyG from Wbetavirus genus bacteriophage Gamma and a few other Wbetavirus genus phages. They are larger than PlyG (351 vs. 233 amino acid residues), contain a signal peptide at their N-termini, and, by prediction, have a different fold of cell binding domain suggesting different structural basis of cell epitope recognition. We purified in a soluble form the modified versions of these endolysins, designated by us LysJ and LysF, respectively, and depleted of signal peptides. Both modified endolysins could lyse the B. anthracis cell wall in zymogram assays. Their activity against the living cells of B. anthracis and other species of Bacillus genus was tested by spotting on the layers of bacteria in soft agar and by assessing the reduction of optical density of bacterial suspensions. Both methods proved the effectiveness of LysJ and LysF in killing the anthrax bacilli, although the results obtained by each method differed. Additionally, the lytic efficiency of both proteins was different, which apparently correlates with differences in their amino acid sequence. Key points • LysJ and LysF are B. anthracis-targeting lysins differing from lysins studied so far • LysJ and LysF could be overproduced in E. coli in soluble and active forms • LysJ and LysF are active in killing cells of B. anthracis virulent strains